2007
DOI: 10.11646/zootaxa.1564.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Annotated checklist of the rotifers (Phylum Rotifera), with notes on nomenclature, taxonomy and distribution

Abstract: Phylum Rotifera comprises about 2030 known species classified in three main groups, the marine Seisonida (3 species), the Monogononta (1570 species) and the unique, exclusively parthenogenetic Bdelloidea with 461 clonal species. Here I present an annotated checklist of the taxon, giving the global distribution of the valid species. This checklist contains over 3,000 available names at the genusand species-group level, including valid names and a non-comprehensive list of synonyms. A number of taxonomic and nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
251
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(269 citation statements)
references
References 18 publications
4
251
0
14
Order By: Relevance
“…The colonial lifestyle is relatively uncommon among Rotifera, being present in only two families for a total of eight genera and approximately 27 species (compared to >2,000 species of solitary rotifers; Segers 2007). The evolution of the colonial lifestyle was examined by Wallace (1987) who concluded that coloniality may have two functions: (1) to amplify feeding eYciency at the individual level through increased water circulation by the total colony (see also Garcia 2004) and (2) to enhance protection from predators (see also Diéguez and Balseiro 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The colonial lifestyle is relatively uncommon among Rotifera, being present in only two families for a total of eight genera and approximately 27 species (compared to >2,000 species of solitary rotifers; Segers 2007). The evolution of the colonial lifestyle was examined by Wallace (1987) who concluded that coloniality may have two functions: (1) to amplify feeding eYciency at the individual level through increased water circulation by the total colony (see also Garcia 2004) and (2) to enhance protection from predators (see also Diéguez and Balseiro 1998).…”
Section: Discussionmentioning
confidence: 99%
“…; Segers 2007) and consists of mostly free-living, microscopic invertebrates characteristic of marine and freshwater environments. Their small size (50-1,500 m) and high abundance makes them especially important in the trophic dynamics of many freshwater ecosystems where they prey on a variety of microbes, phyto-and zooplankton (Arndt 1993), and in turn, are fed upon by numerous invertebrate and vertebrate predators (e.g., Williamson 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomy in rotifers has often been unsteady for most common species, with the description of a large number of subspecies, forms, varieties and doubtful synonymies (Segers, 2007). The main goal of current taxonomy in rotifers is to distinguish proper taxonomic features from morphological variability induced by ecological variation.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to the production of this work, we are developing a database in which the taxonomic and distributional data on which the treatments presented here are based. This on-going task aims not only to provide access to the raw data the FADA experts have compiled, but we envisage developing a web portal containing additional functionalities like, for example, a repository for local distributional data (see Segers, 2007). These services and any supplementary information resulting from the project will be made accessible through http://www.fada.biodiversity.be (Balian et al, 2007).…”
Section: Resultsmentioning
confidence: 99%